Research on Loading and Unloading Resource Scheduling and Optimization of Rail–Road Transportation in Container Terminal Based on "Internet +" —for Ghana Container Port Development Planning. (9th January 2020) - Zhang, Qi; Kwabla, Adjei Courage; Zhuang, Yanhui; Ling, Mingjun; Wei, Yuguang; Yang, Hao
Abstract : Based on the "Internet +" technology, this paper establishes a logistics information platform for the container terminal. Under the premise of the scheduled arrival time and quantity of the truck, this paper aims at minimizing the working time of the loading and unloading equipment and the stay time of the train and truck in the station, and develops a scheduling optimization of loading and unloading model combing equilibrium assignment and flexible scheduling to realize the seamless transfer between rail and road transportation in container terminal. In order to solve the model, a multi-layer coding genetic algorithm with chromosome feasibility is designed to obtain the optimal scheduled time for the truck, and the optimal operation sequence of the gantry crane. Referring to China's container station, this paper takes Takoradi container terminal of Ghana as a case to verify the accuracy and effectiveness of the model and algorithm and provides the medium or long term planning for Ghana's development.